2000
DOI: 10.1007/s002040000118
|View full text |Cite
|
Sign up to set email alerts
|

Phenol sulphotransferase SULT1A1 polymorphism in prostate cancer: lack of association

Abstract: Preliminary evidence suggests that genetic polymorphisms in certain enzymes involved in xenobiotic metabolism and chemical defense could modify a susceptibility to prostate cancer. In the present study, two recently described phenol sulphotransferase SULT1A1 alleles (SULT1A1*1, SULT1A1*2) were investigated using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) approach. Genotyping was performed on DNA isolated from white blood cells from 134 patients with prostate cancer and 184 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
7
19
1
Order By: Relevance
“…However, in the present study, no significant relationship was determined between the His 213 allele and prostate cancer although His 213 allele frequencies were higher in the patients than in the controls. Another study which is in agreement with ours was reported by Steiner et al (15). In contrast, Nowell et al (11) found a positive association between the Arg 213 allele (rapid sulfation allele) and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the present study, no significant relationship was determined between the His 213 allele and prostate cancer although His 213 allele frequencies were higher in the patients than in the controls. Another study which is in agreement with ours was reported by Steiner et al (15). In contrast, Nowell et al (11) found a positive association between the Arg 213 allele (rapid sulfation allele) and prostate cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…His and several cancer types including prosand several cancer types including prostate cancer (9)(10)(11)(12)(13)(14)(15)(16). On the other hand, the findings of these studies remain controversial.…”
mentioning
confidence: 99%
“…From the Medline search using the search terms described earlier, we identified 34 case -control studies for SULT1A1 Arg 213 His polymorphism (Seth et al, 2000;Steiner et al, 2000;Bamber et al, 2001;Zheng et al, 2001Zheng et al, , 2003Ozawa et al, 2002;Wang et al, 2002;Nowell et al, 2002aNowell et al, , 2004Tang et al, 2003;Wu et al, 2003;Chacko et al, 2004;Hung et al, 2004;Langsenlehner et al, 2004;Liang et al, 2004;Tiemersma et al, 2004;Tsukino et al, 2004;Boccia et al, 2005Boccia et al, , 2006 with different types of cancers including UADT TRC, which is biologically more plausible, the studies included in meta-analysis were categorised according to the site of primary cancer as UADT TRC, genitourinary, breast, colorectal and other cancer sites. All the studies were further analysed with respect to genotypes, source of controls, ethnicity and carcinogen exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Steiner et al 8 studied the association between the SULT1A1 polymorphism and prostate cancer in a Caucasian population and found similar frequencies of the variant his allele in 134 cases and 184 controls (35.1% vs. 39.1%). After investigating 444 breast cancer patients and 227 controls, Seth et al 10 found the frequency of the his allele (28.6%) in breast cancer patients was similar to that (30.8%) in controls; thus, no association was observed (p ϭ 0.69).…”
Section: Discussionmentioning
confidence: 97%
“…8 -10 In one study, a lack of association between this polymorphism and prostate cancer was noted in 134 cases and 184 controls. 8 Two large-scale studies have investigated the effect of this polymorphism on breast cancer risk in women. 9,10 Although Zheng et al 9 found his/his to be an independent risk factor for breast cancer in women, Seth et al 10 did not.…”
mentioning
confidence: 99%